Biogeographic role of the Indonesian Seaway implicated by colonization history of purpleback flying squid, Sthenoteuthis oualaniensis (Lesson, 1830), in the Indo-Pacific Ocean - He, Lijun; Xu, Shasha; Weese, David A.; Zhang, Jie; Ren, Huimin; Tang, Fenghua; Sha, Zhongli; Zhang, Jing (Frontiers in Marine Science, 2022)
As a biodiversity hotspot, the East Indies (Coral) Triangle possesses maximum biodiversity on the earth. However, evolutionary hypotheses around this area remained controversial: e.g., center of origin, center of accumulation and center of overlap were supported by different species, respectively. This study aims to answer evolutionary influence of the Indonesian Seaway in the Coral Triangle's biodiversity center through recovering evolutionary origin of a wide-ranging ommastrephids squid (Sthenoteuthis oualaniensis) based on integrated DNA molecular and oceanographic clues from the Indo-Pacific. Three new clades were revealed: viz. clade I from the South China Sea, clade II from the northern East Indian Ocean and clade III from the southern East Indian Ocean. These two Indian Ocean clades formed a monophyly closely related to clade IV from the Central-Southeast Pacific. Clade VI from the central Equatorial Pacific and clade V from the northern Eastern Pacific sit in basal positions of phylogenetic trees. Ancestral Sthenoteuthis was inferred to have originated from the Atlantic Ocean and sequentially dispersed to the northern East Pacific, Central Equatorial Pacific and West Pacific through the open Panama Seaway and westward North Equatorial Current transport. The East Indian Ocean was likely colonized by ancestral population of clade IV from the Southeast Pacific. Westward South Equatorial Circulation could have promoted transoceanic migration of S. oualaniensis through the wide palaeo-Indonesian Seaway. Sea level regression since Miocene and closure of the Indonesian Seaway at 4-3 Ma were responsible for population genetic differentiation of S. oualaniensis in the Indo-Pacific. Therefore, the Indonesian Gateway played an important role in influencing marine organisms migration and population differentiation through controlling and reorganizing circulations in the Indo-Pacific.